N-Acetylcysteine as an antioxidant and disulphide breaking agent: the reasons why. (3rd July 2018) - Aldini, Giancarlo; Altomare, Alessandra; Baron, Giovanna; Vistoli, Giulio; Carini, Marina; Borsani, Luisa; Sergio, Francesco
Abstract: The main molecular mechanisms explaining the well-established antioxidant and reducing activity of N-acetylcysteine (NAC), the N -acetyl derivative of the natural amino acidl -cysteine, are summarised and critically reviewed. The antioxidant effect is due to the ability of NAC to act as a reduced glutathione (GSH) precursor; GSH is a well-known direct antioxidant and a substrate of several antioxidant enzymes. Moreover, in some conditions where a significant depletion of endogenous Cys and GSH occurs, NAC can act as a direct antioxidant for some oxidant species such as NO2 and HOX. The antioxidant activity of NAC could also be due to its effect in breaking thiolated proteins, thus releasing free thiols as well as reduced proteins, which in some cases, such as for mercaptoalbumin, have important direct antioxidant activity. As well as being involved in the antioxidant mechanism, the disulphide breaking activity of NAC also explains its mucolytic activity which is due to its effect in reducing heavily cross-linked mucus glycoproteins. Chemical features explaining the efficient disulphide breaking activity of NAC are also explained.